Working memory updating training reduces state repetitive negative thinking: Proof-of-concept for a novel cognitive control training. (July 2021) - Roberts, Henrietta; Mostazir, Mohammod; Moberly, Nicholas J.; Watkins, Edward R.; Adlam, Anna-Lynne
Abstract: Repetitive negative thinking (RNT) is a proximal risk factor implicated in the onset and maintenance of common mental health problems such as depression and anxiety. Adolescence may be a key developmental window in which to target RNT and prevent the emergence of such disorders. Impairments in updating the contents of working memory are hypothesised to causally contribute to RNT, and some theorists have suggested these difficulties may be specific to the manipulation of negative information. The present study compared the effects of computerised adaptive working memory updating training (in which the task becomes more difficult as performance improves) to a non-adaptive control task in reducing levels of RNT. 124 healthy young people were randomised to 20 sessions of (i) working memory updating training using neutral stimuli, (ii) working memory updating training using negative stimuli, or (iii) non-adaptive working memory updating training. Adaptive working memory updating training using neutral, but not negative, stimuli resulted in significant improvements to working memory updating for negative material, as assessed using an unpractised task, and significant reductions in susceptibility to state RNT. These findings demonstrate proof-of-concept that working memory updating training has the potential to reduce susceptibility to episodes of state RNT. Highlights: 124 young people participated in a novel working memory updating training. Training using neutral, but not negative, stimuli improved working memory updating. Training using neutral stimuli also reduced repetitive negative thinking. Working memory updating causally influences repetitive negative thought. Targeted working memory updating training may be a valuable preventive approach.